Optimization of rebaudioside a yield from stevia rebaudiana cultivated on bris soil and its biological activities - Asrul Afandi Ab. Halim (2015)
Stevia rebaudiana is a sweet perennial herb which has been widely cultivated through the world for the sweet diterpene glycosides. S. rebaudiana has been applied as substitutes for sucrose, for treatment of diabetes mellitus, obesity, hypertension and caries prevention. Among the diterpene glycoside, rebaudioside A showed the lowest bitterness and the taste is close to sucrose. In this study two varieties MSR012 and MSR007 obtained from MARDI, Bachok, Kelantan were studied to maximize the yield of rebaudioside A from S. rebaudiana grown on BRIS soil. In order to find the best harvesting time of S. rebaudiana, proximate analysis were done on S. rebaudiana leaves from different maturity stage, i.e., before flowering (30-35days), flowering time (50-60 days) & over mature (70- 90days) of new apical stem grown on 2 year old plant. Separation method by solvent extraction followed by crystallization and re- crystallization of rebaudioside A in amorphous form were done in order to obtain sweetener which consist mainly bioactive compound, rebaudioside A. Moisture, ash, reducing sugar, non-reducing sugar and total carbohydrate were found maximum in variety MSR007 before flowering stage with 8.45%, 7.17%, 4.45%, 8.45%, and 13.65% respectively. Percentages of rebaudioside A were found maximum just before flowering stage with 3.45% followed by over matured stage with 2.20% and during flowering time with 1.82%.